β-Lactam rearrangements into five-membered heterocycles - Dražić, Tonko; Roje, Marin (Chemistry of heterocyclic compounds, 2017)
Open image in new windowβ-Lactams are compounds of great importance in both medicinal chemistry and as building blocks for the synthesis of different types of biologically relevant compounds. Among other transformations, β-lactams can easily be rearranged into five-membered heterocycles. The rearrangement occurs by cleavage of any of four β-lactam bonds. The type of final five-membered ring mainly depends on the side chain groups of starting β-lactam, as well as reaction conditions. Furthermore, rearrangement reactions are often stereoselective, with product rings retaining the stereochemistry of β-lactams. The ability of β-lactams to form a variety of diversely decorated five-membered heterocycles, often in stereoselective fashion, makes this class of compounds attractive synthons in organic chemistry. This review covers the progress in the field within last ten years.